The native/nonnative conundrum revisited - Medgyes Péter („RIK-U” Kft., 2018)
Abstract. In my book, ‘The non-native teacher’ (1994), I argued that nonnative-speaking teachers of English were unable to emulate native speakers in terms of their English-language competence. At the same time I also claimed that nonnatives were in possession of certain attributes that may well offset their linguistic handicap. To prove my point I put forward two sets of hypotheses. Since my publication a lot has happened concerning the native/nonnative dilemma and English language teaching in general. With a new paradigm looming large, I propose a 9-point action plan for deliberation.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: The non-native teacher; english teacher; english language